Багатоагентні системи як спосіб моделювання та проектування - Охотников, О. С. (ХНУРЕ, 2020)
An analysis of the problem of using multi-agent systems revealed the lack of a unified approach to the design and creation of a convenient way of modeling distributed systems. Multi-agent systems provide a useful modeling framework in systems consisting of a large number of agents who interact with each other in various ways. In these models, the agents change their actions as a result of events in the process of interaction. The behavior of the whole system depends on these interactions between agents, which can be represented in a model. Multi-agent system are used to set up spatial models, which integrate social and ecological dimensions.
Keywords: багатоагентна система; графічні процеси